EKSPLORASI ETNOMATEMATIKA PADA RUMAH ADAT MBARU GENDANG DI DESA WAE AJANG KECAMATAN SATARMESE KABUPATEN MANGGARAI - Efronius Nardo; Ningsih Ningsih; Maria Fatima Mei (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2023)
Education and culture are two inseparable components like two sides of a coin. People often do not realize that they have applied various mathematical concepts in their customs and culture. One of the cultural heritages of Manggarai passed down by our ancestors to this day is the Manggarai traditional house. This study aims to describe the concept of plane geometric shapes in the Mbaru Gendang traditional house in Cambir village. This research is descriptive qualitative research. The subjects of this study were informants namely tu'a gendang, tu'a tanga and community leaders. The instruments used were human instruments, interview guidelines and documentation. Collecting data using interviews and documentation. Data analysis uses three activities according to Miles and Huberman, namely data reduction, data presentation and conclusion. The results of this study indicate that the ethnomathematics in the Mbaru Gendang Traditional House in Cambir village has mathematical concepts, namely (1) On the tent board (deck) of the Mbaru Gendang traditional house are: Equilateral Triangles, Trapezoid and Circles. (2) On the bolo section (Front Door) and the ventilation for the bolo of the Mbaru Gendang traditional house are in the form of Rectangle and Belaketupat. (3) On the window ventilation and later pillars of the Mbaru Gendang traditional house, these are: Squares and Right-angled Triangles.